An Unusual Case of Sudden Collapse in the Immediate Postoperative Period in a Young Healthy Female with Myxofibroma of the Maxilla - Manila Singh; Saket Singh (Case Reports in Anesthesiology)
Benign myxofibromas of heart are well known to cause systemic inflammatory mediator release causing multiple complications ranging from fever and widespread effusions to DIC and shock. We report that in a particular case of maxillary myxofibroma, a shock-like state and widespread serous cavities effusion presented in the immediate postoperative period. The occurrence was possibly due to release of inflammatory mediators by the tumour, disseminated during tumour resection causing diffuse capillary leak, precipitated by fluid resuscitation, leading to decrease in plasma oncotic pressure.